Рекурентные алгоритмы для решения интегро-диференциальных уравнений вязкоупругих систем - Корнеев, А.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
The paper discusses algorithms for solving integro-differential equations based on recurrence algorithms for problems in the theory of viscoelasticity.